Trajetórias de lutas e formação agrária no Oeste catarinense (2002-2020) - Bastiani , Tânia Mara de (2020)
The process of formation and consolidation of the small property in Western Santa Catarina did not welcome all landless families, because, from the first moment, it was founded on the expropriation of indigenous and caboclos, which took place through the formation of “farms to create”, of the from opening up paths for troops and the action of colonizers, thus inaugurating land concentration in the region. Moreover, in the midst of the advance of capitalism in the countryside, represented by the ideas of "modernization" and "agribusiness", many settlers also ended up losing their land, due to the debts they accumulated to try to adapt to new productive practices. In view of these issues, we sought to deconstruct the hegemonic social representation of the agrarian formation of the place as formed exclusively by the small property so that it would be possible to see that the struggle for land is part of the agrarian constitution of the region, as well as, the understanding of the making of the MST in this place. Through oral and written sources, the historicization of the title of the Barra Grande farm and the life trajectory of the residents of the Dom José Gomes settlement, in Chapecó/SC, we sought to analyze a particular case that could exemplify the dynamics of land concentration and the struggle of the MST in the region. To this end, we address the occupation that took place in 2002, the camp and the settlement, as well as the new dimensions assumed by the struggle after the conquest of the land. Understanding the struggle for land, in general, and that of the MST, in particular, as part of the agrarian constitution of in Western Santa Catarina, not only addresses the trajectories of the expropriated of the land, but also dispels any conceptions based on explanations that glorify colonization.